2000
DOI: 10.1002/(sici)1097-4628(20000307)75:10<1255::aid-app6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and adsorption properties for metal ions of mesocyclic diamine-grafted chitosan-crown ether

Abstract: ABSTRACT:A new type of grafted chitosan-crown ether was synthesized using mesocyclic diamine crown ether as the grafting agent. The C2 amino group in chitosan was protected from the reaction between benzaldehyde and chitosan to form N-benzylidene chitosan (CTB). After reaction with mesocyclic diamine crown ether of the epoxy propane group to give mesocyclic diamine-N-benzalidene chitosan (CTBA), the Schiff base was removed in a dilute ethanol hydrochloride solution to obtain chitosan-crown ether (CTDA). Its st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The limitations can be alleviated if the CRs are either chemically reacted or grafted onto man-made polymers. It is predicted that CR-based polymers would form stronger complex with better selectivity for metal ions than corresponding crown ethers [611]. In fact, CR-based materials synthesized by these methods are reported to exhibit unique features and properties, and have been successfully used in a variety of applications including as membranes for extraction of heavy metal ions and for selective ion transport [611].…”
Section: Introductionmentioning
confidence: 99%
“…The limitations can be alleviated if the CRs are either chemically reacted or grafted onto man-made polymers. It is predicted that CR-based polymers would form stronger complex with better selectivity for metal ions than corresponding crown ethers [611]. In fact, CR-based materials synthesized by these methods are reported to exhibit unique features and properties, and have been successfully used in a variety of applications including as membranes for extraction of heavy metal ions and for selective ion transport [611].…”
Section: Introductionmentioning
confidence: 99%
“…Both linear and non-linear regression analyses produce different models as the best fitting isotherm for the given set of data, thus indicating a significant difference between the analytical methods. In attempting to compare the maximum amounts of divalent copper, lead and cadmium sorbed in chitosan and chemically modified derivatives [9,28,[36][37][38][39][40][41][42], significant examples are listed in Table 5. The biopolymer/cation interactive effect depends not only on the properties of the sorbent and sorbate, but also on various environmental aspects such as pH, ionic strength, temperature, sorbent concentration and contact time.…”
Section: Sorption Studymentioning
confidence: 99%
“…For copper the values varied from 0.49 to 0.91 mmol g -1 ; also it includes chitosan pendant chains containing polyphosphate derivative [39], Table 3 Constants (Cnst) of the Freundlich (n and K F ) and Temkin (b and K T ) models (Mod), correlation coefficient (R 2 ) and error function (SE and v 2 ) for interaction of divalent copper, lead and cadmium with chitosan at 298 ± 1 K, using linear method crown ethers [40,41], cross-linked with epichlorohydrin [9] and pyridylmethyl derivative [42], which higher amount sorbed expressed its effectiveness in bond formation. For glycidylmethacrylate pendant chain moiety expanded with triamine (CHglyc) [16] also gave higher value of 3.59 mmol g -1 for this cation sorption.…”
Section: Sorption Studymentioning
confidence: 99%
“…The selective chelating properties exhibited by crown ethers towards metal ions have led to their incorporation into chitosan polymer matrices to improve capacity for metal ion adsorption [1][2][3], enhance selective pollutant removal [4,5], and thus wastewater remediation [6,7]. While many authors have chemically modified crosslinked chitosan with crown ethers [5,6,[8][9][10][11][12][13][14][15][16][17], and shown the advantage of combining crown ethers with chitosan [5,8,9,18,19], only a few have used the crown ether as the crosslinker for chitosan [7,18,[20][21][22][23][24] and fewer have used the nitrogen containing azacrown ethers [25]. Using the azacrown ether as the crosslinker has the advantage that the consumption of the -NH 2 chelating group of the chitosan might be compensated by the azacrown ether chelating property.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nitrogen containing azacrown ethers are particularly interesting due to their stronger complexation properties for heavy-metal ions [1,[26][27][28] than the all-oxygen crowns, which strongly complex alkali and alkaline earth metal [26,28]. For example, Ding et al [25] used N,N -diallyl dibenzo-18-crown-6 crown to crosslink chitosan and revealed that these materials performed better in metal ion adsorption than neat Ch owing to the presence of the crown ethers [15,16,22,23]. Structural elucidation of the products suggested that these crown ethers crosslink chitosan, although no report of gel content or network formation was presented in this work and others [10,11,15,16,20,23].…”
Section: Introductionmentioning
confidence: 99%